The Impact of Human Resource Information System Automation on Efficiency and Performance in Tanzania’s Public Universities (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
This study assessed the impact of the Human Resource Information System in enhancing organisational performance at the University of Dar es Salaam and Mbeya University of Science and Technology in Tanzania. Adopting a quantitative research design, the study employed a census approach to collect data from 204 purposively selected supervisors in both universities. Descriptive analysis and partial least squares structural equation modeling (PLS-SEM) were utilized for the data analysis. The findings revealed a positive and significant relationship between HRIS automation services and organisational performance, with a regression coefficient of 0.220 and a p-value of 0.000, signifying that increased HRIS automation services enhance performance. The study concludes that HRIS automation is integral to organisational performance and recommends strengthening ICT infrastructure, fostering employee engagement through training and resource allocation, and implementing evaluation mechanisms to align HRIS with institutional objectives. These measures will enhance HRIS efficiency and contribute to improved institutional effectiveness.